Specific Characteristics of Professional Self-Determination of Students - Shoyimova Shoira Sanakulovna (Researchparks Publishing, 2023)
Today, young people who are starting an independent life should have the most up-to-date education, high intellectual and physical fitness, deep knowledge of the scientific, technical and economic bases of production, and a conscious creative attitude to work. In this article, opinions and suggestions on some issues of solving pedagogical-psychological issues regarding professional formation of students from school age are presented.